Three feminizing Wolbachia strains in a single host species: comparative genomics paves the way for identifying sex reversal factors - Grève, Pierre; Moumen, Bouziane; Bouchon, Didier (Frontiers in Microbiology, 2024)
Endosymbiotic bacteria in the genus Wolbachia have evolved numerous strategies for manipulating host reproduction in order to promote their own transmission. This includes the feminization of males into functional females, a well-studied phenotype in the isopod Armadillidium vulgare. Despite an early description of this phenotype in isopods and the development of an evolutionary model of host sex determination in the presence of Wolbachia, the underlying genetic mechanisms remain elusive. Here we present the first complete genomes of the three feminizing Wolbachia (wVulC, wVulP and wVulM) known to date in A. vulgare. These genomes, belonging to Wolbachia B supergroup, contain a large number of mobile elements such as WO prophages with eukaryotic association modules.Taking advantage of these data and those of another Wolbachia-derived feminizing factor integrated into the host genome (f element), we used a comparative genomics approach to identify putative feminizing factors. This strategy has enabled us to identify three prophageassociated genes secreted by the Type IV Secretion System: one ankyrin repeat domaincontaining protein, one helix-turn-helix transcriptional regulator and one hypothetical protein. In addition, a latrotoxin-related protein, associated with phage relic genes, was shared by all three genomes and the f element. These putative feminization-inducing proteins shared canonical interaction features with eukaryotic proteins. These results pave the way for further research into the underlying functional interactions.